THE APPLICATION OF ECONOMIC AND MATHEMATICAL METHODS FOR OPTIMIZATION OF ACTIVITIES OF ADVERTISING AGENCY - Andrei A. Romanov (Статистика и экономика, 2016)
The accumulated experience in solving practical problems in the organization of advertising activity allows allocating four classes of problems focused on ap-plication of economic and mathematical methods - resource allocation, queuing problem, network planning and combina-torial problems